2017
DOI: 10.1177/1947603516686145
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Biochemical Bone Turnover Markers and Bone Mineral Density in Thin and Normal-Weight Children

Abstract: Objective There is scant research examining the prevalence of thinness in early childhood, despite its potential negative consequences for health and development across the life course. The objective of this study was to assess bone status through measurement of bone mineral density and biochemical bone turnover markers, with special attention paid to carboxylated (c-OC) as well as undercarboxylated (uc-OC) forms of osteocalcin, in the groups of thin and normal-weight children. Design The study included 80 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
2
6
1
1
Order By: Relevance
“…Our results did not support previously described positive correlations between OC and height and weight [10, 14], between CTX and weight [14] and height [13, 38] or the finding of decreased OC values in obese when compared to healthy weight children [11, 12]. However, in accordance to our findings, a number of other studies have contributed with evidence of a lack of association between height, weight or BMI and OC [9, 10, 13, 14, 39, 44] and height or BMI and β-CTx [44]. Increased formation markers in taller and heavier children are likely reflecting greater growth velocity, inducing increased bone formation in response to greater mechanical strain [13, 32].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results did not support previously described positive correlations between OC and height and weight [10, 14], between CTX and weight [14] and height [13, 38] or the finding of decreased OC values in obese when compared to healthy weight children [11, 12]. However, in accordance to our findings, a number of other studies have contributed with evidence of a lack of association between height, weight or BMI and OC [9, 10, 13, 14, 39, 44] and height or BMI and β-CTx [44]. Increased formation markers in taller and heavier children are likely reflecting greater growth velocity, inducing increased bone formation in response to greater mechanical strain [13, 32].…”
Section: Discussioncontrasting
confidence: 99%
“…We found a positive correlation between OC and β-CTx, in agreement with findings in other samples of prepubertal children [17] but in contrast with one study including 5 to 10 year-old children [14]. Positive relationships between bone-specific formation and resorption markers are expected, and reflect the nature of bone turnover as a tightly regulated dynamic mechanism of formation and resorption [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Complementarily, low grade inflammation related to obesity promotes adipogenesis in the detriment of osteoblastogenesis and calcium absorption, increasing the risk of fractures and osteoporosis. [42][43][44] In a study presented by Ambroszkiewicz et al 45 higher CTX-I levels indicated a defective bone formation in thin children, compared to normal-weight peers. Moreover, the ratio of the carboxylated OC/undercarboxylated OC, as well as the BMD were significantly lower in thin children when compared to the normal-weight group.…”
Section: Predictive Roles Of Btms In Osteoporosis-related Pathologiesmentioning
confidence: 96%
“…Ovo je ukazalo da negativan energetski balans, praćen smanjenjem vrijednosti BMI i vjerovatno smanjenjem procenta mišićnog tkiva, ima manji osteogeni efekat, smanjenim opterećenjem sopstvenom težinom, a vjerovatno i smanjenim efektom trakcije od strane mišićnog tkiva. Do sličnog rezultata je došla i nedavna studija Ambroszkiewicz-a i saradnika [33] kojom je utvrđeno da eumenoreične djevojke adolescentne dobi koje imaju manji BMI imaju veće vrijednosti markera razgradnje kosti CTX, a manje vrijednosti osteokalcina. Slične tvrdnje je pokazala i nedavna studija Thralls-a i saradnika [34] u kojoj su potvrdili da smanjene vrijednosti opštih antropometrijskih indeksa (BMI I IBW) mogu biti prediktori smanjene vrijednosti BMD kod aktivnih sportistkinja.…”
Section: Diskusijaunclassified